In vitro mechanical fatigue behavior of poly‐ɛ‐caprolactone macroporous scaffolds for cartilage tissue engineering: Influence of pore filling by a poly(vinyl alcohol) gel. Issue 5 (17th September 2014) - Panadero, J. A.; Vikingsson, L.; Gomez Ribelles, J. L.; Lanceros‐Mendez, S.; Sencadas, V.
Abstract Polymeric scaffolds used in regenerative therapies are implanted in the damaged tissue and submitted to repeated loading cycles. In the case of articular cartilage engineering, an implanted scaffold is typically subjected to long‐term dynamic compression. The evolution of the mechanical properties of the scaffold during bioresorption has been deeply studied in the past, but the possibility of failure due to mechanical fatigue has not been properly addressed. Nevertheless, the macroporous scaffold is susceptible to failure after repeated loading‐unloading cycles. In this work fatigue studies of polycaprolactone scaffolds were carried by subjecting the scaffold to repeated compression cycles in conditions simulating the scaffold implanted in the articular cartilage. The behavior of the polycaprolactone sponge with the pores filled with a poly(vinyl alcohol) gel simulating the new formed tissue within the pores was compared with that of the material immersed in water. Results were analyzed with Morrow's criteria for failure and accurate fittings are obtained just up to 200 loading cycles. It is also shown that the presence of poly(vinyl alcohol) increases the elastic modulus of the scaffolds, the effect being more pronounced with increasing the number of freeze/thawing cycles. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1037–1043, 2015.